Increasing Cost Efficiency in Adult Spinal Deformity Surgery: Identifying Predictors of Lower Total Costs. Issue 1 (1st January 2022) - Passias, Peter G.; Brown, Avery E.; Bortz, Cole; Alas, Haddy; Pierce, Katherine; Ahmad, Waleed; Naessig, Sara; Lafage, Renaud; Lafage, Virginie; Hassanzadeh, Hamid; Labaran, Lawal A.; Ames, Christopher; et al.
Abstract : Study Design: Retrospective study of a prospective multicenter database. Objective: The purpose of this study was to identify predictors of lower total surgery costs at 3 years for adult spinal deformity (ASD) patients. Summary of Background Data: ASD surgery involves complex deformity correction. Methods: Inclusion criteria: surgical ASD (scoliosis ≥20°, sagittal vertical axis [SVA] ≥5 cm, pelvic tilt ≥25°, or thoracic kyphosis ≥60°) patients >18 years. Total costs for surgery were calculated using the PearlDiver database. Cost per quality-adjusted life year was assessed. A Conditional Variable Importance Table used nonreplacement sampling set of 20, 000 Conditional Inference trees to identify top factors associated with lower cost surgery for low (LSVA), moderate (MSVA), and high (HSVA) SRS Schwab SVA grades. Results: Three hundred sixtee of 322 ASD patients met inclusion criteria. At 3-year follow up, the potential cost of ASD surgery ranged from 57, 606.88 to 116, 312.54. The average costs of surgery at 3 years was found to be 72, 947.87, with no significant difference in costs between deformity groups ( P > 0.05). There were 152 LSVA patients, 53 MSVA patients, and 111 HSVA patients. For all patients, the top predictors of lower costs were frailty scores <0.19, baseline (BL) SRS Activity >1.5, BL Oswestry Disability Index <50 (all P < 0.05). For LSVA patients, no history of osteoporosis, SRS Activity scores >1.5, age <64, were the top predictors of lower costs (all P < 0.05). Among MSVA patients, ASD invasiveness scores <94.16, no past history of cancer, and frailty scores <0.3 trended toward lower total costs ( P = 0.071, P = 0.210). For HSVA, no history of smoking and body mass index <27.8 trended toward lower costs (both P = 0.060). Conclusion: ASD surgery has the potential for improved cost efficiency, as costs ranged from 57, 606.88 to 116, 312.54. Predictors of lower costs included higher BL SRS activity, decreased frailty, and not having depression. Additionally, predictors of lower costs were identified for different BL deformity profiles, allowing for the optimization of cost efficiency for all patients. Level of Evidence: 3 Abstract : With an increased focus on cost and resource utilization in health care, there is paucity in the literature on preoperative factors associated with lower total adult spinal deformity surgery costs. This study identified decreased baseline deformity, physical disability, and frailty as significant predictors of experiencing lower total costs surgery by 3 years.